Pengaruh Literasi Spasial dalam Pembelajaran IPS di SD Kelas Tinggi: Sebuah Telaah Literatur - ROZIMAN ROZIMAN; Serlina Agustin; Tin RUSTINI (UIN Fatmawati Sukarno Bengkulu, 2023)
Learning activities have an impact on student learning outcomes. With the use of relevant learning models, it will facilitate the process of teaching and learning activities to run well in accordance with learning outcomes. This study aims to find out how the influence of spatial literacy in the social studies learning process in high school elementary school. The research method used in this research is literature study with a qualitative approach and reduction technique. The results of the study show that Spatial Literacy can invite students to practice education, for example by using illustrations of map diagrams, observing detailed designs of demonstration sketches. In addition, the children were invited to make a mind mapping project, and analyze how things work, how to move, and an imitation model of the relationship between parts. Spatial literacy in social studies learning can also improve cognitive intelligence in children, improve students' affective and psychomotor skills, but must use the right learning media.